Distribution of nucleotide variants in the DNA sequence of ERCC1 and XRCC1 genes and the effect of phenotype in patients with gastric cancer - Asgerov, Elmir; Şenol, Özgür; Güler, Adem; Berdeli, Afig (Turkish Journal of Gastroenterology, 2019)
Abstract Background/Aims: Gastric cancers vary across countries and ethnic groups. They are the second most common type of cancer worldwide. Dietary and non-dietary factors as well as genetic and epigenetic alterations of many mechanisms are implicated in the development of gastric cancer. We aimed to determine the sequence of possible nucleotide changes, polymorphisms, and mutations, and to establish genotype and phenotype relation by performing whole DNA sequence analysis of the XRCC1 and ERCC1 genes belonging to base excision repair (BER) and nucleotide excision repair (NER) family of DNA repair genes in patients with gastric cancer. Materials and Methods: We included 50 patients of both sexes who had received diagnosis of gastric cancer and 50 healthy people who showed same demographic traits that forms the control group. We analyzed the ERCC1 and XRCC1 genes by DNA sequence analysis on both groups. After the analysis, we compared the genotype-phenotype relation. Results: Neither patients nor the control group has any nucleotide replacement in any exon of ERCC1 genes. We could not detect significant difference between patients and healthy groups when we correlated genotype contribution of mutations Arg194Trp, Arg208His, Arg399Gln detected in the XRCC1 gene and allele frequency. Conclusion: According to our study, the ERCC1 gene in Turkish population is not getting mutation in patients with gastric cancer and healthy individuals. Three mutations were detected in the XRCC1 gene, and these mutations were not associated with gastric cancer. Cite this article as: Asgerov E, Şenol Ö, Güler A, Berdeli A. Distribution of nucleotide variants in the DNA sequence of ERCC1 and XRCC1 genes and the effect of phenotype in patients with gastric cancer. Turk J Gastroenterol 2019; 30(6): 517-23.